2010
DOI: 10.3342/ceo.2010.3.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in a Cross Sectional Study of Age-related Hearing Loss in Korean

Abstract: ObjectivesThe purpose of this study was to obtain sex- and age-specific reference level for hearing threshold of normal aging in Korean and to determine if the rate of change in pure-tone hearing thresholds differed by sex.MethodsSubjects were clients who visited the Health Promotion Center, Daegu Fatima Hospital, Daegu, Korea, from January 2004 to September 2005. Pure-tone audiometric measures were obtained from 3,470 subjects who also completed a hearing questionnaire. The slope of a linear regression was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
48
2
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 15 publications
8
48
2
8
Order By: Relevance
“…These findings corroborate national and international studies which have shown predominance of occurrence of hearing loss in male subjects (7,(16)(17)(18)(19) . Every subject of this survey related some kind of audiological complaint during the anamnesis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These findings corroborate national and international studies which have shown predominance of occurrence of hearing loss in male subjects (7,(16)(17)(18)(19) . Every subject of this survey related some kind of audiological complaint during the anamnesis.…”
Section: Discussionsupporting
confidence: 91%
“…Various subjects in this survey reported noise exposure. A few works have shown that men are more exposed to noise than women (17,23) . This could explain a greater proportion of hearing loss among male subjects in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, more than 70% of the sample exhibited mild-to-moderate hearing loss (Table 4), with a mild downward sloping configuration in both groups (Table 3). These findings corroborate the results of other studies that investigated hearing in older adults 10,23,24,29 . As presbycusis is associated with aging, being caused by auditory degeneration of the basal portion of the cochlea 12,24 , the predominance of sensorineural hearing loss attended by gradual affection of the audibility thresholds was expected, as the high frequencies are the most severely affected in presbycusis.…”
supporting
confidence: 83%
“…The results of speech audiometry were classified according to Jerger, Speaks & Trammell (1968) 22 . condition impairs the ability to understand speech 4,10 . From the audiological perspective, it is characterized by sensorineural hearing loss, with the auditory threshold for high frequencies affected.…”
Section: Introductionmentioning
confidence: 99%
“…16 Lee dkk. 5 dalam penelitian sebelumnya menemukan hubungan antara usia dan penurunan ambang dengar pada usia lanjut.…”
Section: Pembahasanunclassified